INVESTIGATING THE ROLE OF ESTRADIOL AND THE MUCOSAL MICROENVIRONMENT ON Th17 RESPONSES PRIMED BY DENDRITIC CELLS IN THE FEMALE GENITAL TRACT - Anipindi, Varun Chaitanya (My University, 2016)
Clinical and experimental studies have shown that estradiol (E2) can enhance protection against sexually transmitted infections such as HSV-2 and HIV-1. Antigen presenting cells (APCs) such as Dendritic cells (DCs) are critical for generating immune responses against these infections, and it is unclear whether unique factors present in the genital mucosa can influence immune responses by directly modulating the phenotype and function of local APCs. To address this, I hypothesized that sex hormones, such as E2 and innate factors in the local microenvironment can regulate the phenotype and function of vaginal APCs. The work summarized in this thesis addressed this central hypothesis. In the first section of the thesis, I examined whether vaginal APCs were distinct in their phenotype and function compared to those in other mucosal tissues or spleen. The results show that the vagina was enriched in CD11c+ CD11b+ MHCII− DCs. Functionally, vaginal tissue cells (TC) and CD11c+ DCs were more potent inducers of Th17 responses in co-cultures with CD4+ T cells, compared to lung, small intestine or spleen APCs. E2 was critical for the conditioning of vaginal DCs to prime these Th17 responses through an IL-1-dependent pathway, indicating that sex hormones such as E2 can directly influence the function of vaginal APCs. In the next section, I determined whether other co-factors in the genital microenvironment such as microflora and innate lymphocytes could also influence vaginal APC functions. We found that while microflora was not essential, IL-17 produced by innate lymphocytes was critical for the induction of IL-1 from DCs, and consequently for potentiating Th17 responses. Finally, I attempted to develop an in vivo mouse model where the effect of E2 on vaginal APCs could be examined in the context of genital HSV-2 infection. I tested a 7-day injectable E2 and a 21-day E2 pellet delivery model, and found that both regimes had limitations for examining E2-effects on anti-viral responses. Yet, subsequent to the work done in this thesis, we were able to confirm our observations of E2-conditioned Th17 responses in vivo in an intranasal immunization model utilizing E2 pellet delivery, and thereby addressed the mechanism underlying enhanced anti-viral protection following E2-treatment. In conclusion, this is the first study to show the effect of E2 on genital tract APCs and their ability to prime Th17 responses. It provides future avenues to examine whether modulation of this microenvironment can help optimize vaccine-induced immune responses against STIs. On a more fundamental level, it highlights the need to consider the inherent distinctions in APC populations among different mucosal tissues.
ESTRADIOL INFLUENCES THE FUNCTION OF VAGINAL DENDRITIC CELLS
Keywords: sexually transmitted infections; Th17; sex hormones; estradiol; HSV-2; Dendritic cells; microflora; mucosal immunity; anti-viral responses; antigen presenting cells; microenvironment